2021
DOI: 10.1111/ibi.12955
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal flight calling behaviour of thrushes in relation to artificial light at night

Abstract: Migratory birds are subject to many pressures during their life cycle and many are declining as a consequence. Evidence from North America shows that for species that migrate at night, bright artificial light sources associated with urban areas can disrupt natural movement patterns, leading to direct and indirect fitness consequences. Comparable evidence for species and urban areas in Europe is limited. This study aimed to measure the response of nocturnally migrating thrushes to artificial light at night in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Paumen et al 2022). When compared to other avian studies (Ruff et al 2020, Gillings and Scott 2021, Nolan et al 2022, our trained multilabel CNN achieved similar or even higher levels of classification accuracy ( ≥ 99%) and proved to be highly capable of distinguishing between the 5 different avian species calls herein. The CNN also successfully identified portions of recordings that were devoid of bird calls (i.e., noise clips), resulting in a false positive error rate of zero.…”
Section: T a B L Ementioning
confidence: 51%
“…Paumen et al 2022). When compared to other avian studies (Ruff et al 2020, Gillings and Scott 2021, Nolan et al 2022, our trained multilabel CNN achieved similar or even higher levels of classification accuracy ( ≥ 99%) and proved to be highly capable of distinguishing between the 5 different avian species calls herein. The CNN also successfully identified portions of recordings that were devoid of bird calls (i.e., noise clips), resulting in a false positive error rate of zero.…”
Section: T a B L Ementioning
confidence: 51%
“…Our enhanced recogniser that included seasonal variation (R2) still performed poorly compared to many other machine learning PAM studies (Jahn et al 2017; Bravo et al 2017; Knight and Bayne 2019; Knight et al 2020; Balantic and Donovan 2020; Gillings and Scott 2021). However, our results are comparable to similar studies in tropical environments (Swiston and Mennill 2009; Heinicke et al 2015).…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, flight calls have been used to study how migrants interact with topography and respond to weather (Gesicki et al, 2016;Smith et al, 2014) and light pollution (Gillings & Scott, 2021;Watson et al, 2016;Winger et al, 2019). To our knowledge, no studies have used flight calls to track species-specific phenology (but see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found relationships between acoustic activity and migration intensity measured by radar, thermal cameras or mist nets, but acoustics typically explain little variation in migration intensity (Farnsworth et al, 2004; Horton et al, 2015; Larkin et al, 2002; Sanders & Mennill, 2014). Nevertheless, flight calls have been used to study how migrants interact with topography and respond to weather (Gesicki et al, 2016; Smith et al, 2014) and light pollution (Gillings & Scott, 2021; Watson et al, 2016; Winger et al, 2019). To our knowledge, no studies have used flight calls to track species‐specific phenology (but see e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation